Transforming Pancasila Values Through Civic Education to Address Ethical Challenges in the Use of Artificial Intelligence Technologies - Dita Rosyalita; Salmi Harfi Nabiilah; Darmawati Darmawati (Journal of Mandalika Social Science, 2026)
The rapid development of artificial intelligence (AI) has transformed various aspects of human life while simultaneously creating ethical challenges, including algorithmic bias, privacy concerns, misinformation, and academic dishonesty. These issues highlight the need for ethical guidance that extends beyond technological regulations. This study aims to examine how Pancasila values can be transformed through Civic Education to address ethical challenges in the use of AI technologies. Using a qualitative library research approach, data were collected through a systematic review of books, scholarly journals, policy documents, and relevant scientific literature. The collected data were analyzed using qualitative content analysis to identify patterns, conceptual relationships, and key themes. The findings indicate that the five principles of Pancasila complement global AI ethics by emphasizing humanity, justice, democracy, unity, and social responsibility. Furthermore, Civic Education serves as an effective medium for integrating these values into AI literacy, fostering responsible digital citizenship, ethical decision-making, and sustainable technology use. This study contributes a conceptual framework for strengthening AI ethics through culturally grounded civic education.